The social impact of technology on millennials and consequences for higher education and leadership - Au-Yong-Oliveira, Manuel (2018)
Millennials interact with technology like no other generation before them and this is affecting how they want to be taught in higher education and how they want to lead and expect to be led in organizations, after graduating. Though stating that they want to be enlightened in academia, some qualitative comments from millennials indicate the opposite, namely that they want to be prepared but also to be kept naïve as to what business really entails. This is expected to help keep motivation levels high, as motivation is seen to be the key element to success in life. Millennials expect also to be led authentically and to be treated as valued human beings. This is in contrast to the current autocratic leadership profile found predominantly in Portuguese organizations, at the time of writing. This study had a sample of one hundred and eleven millennial students who answered a survey on attitudes towards leadership and their desired approach to higher education. Three interviews with seasoned executives were also performed, to establish a contrast and see other perspectives. With this research, we conclude that we may be in the presence of a hard working millennial generation, contrary to previous research findings which has indicated that they are lazy. Finally, information technology (IT) is a precious partner in class, in particular Padlet.com, Moodle, and online News Forums, as well as the challenge to create original videos about course content. Future research should focus on how technology has made society more transparent with employees wanting more democratic leaders in times when hierarchies are seen to hinder rather than aid productivity levels.